2021
DOI: 10.1002/ldr.4061
|View full text |Cite
|
Sign up to set email alerts
|

Use of multifrequency (C‐band and L‐band) SAR data to monitor peat subsidence based on time‐series SBAS InSAR technique

Abstract: Peatlands in tropical regions like Indonesia are undergoing irreversible subsidence due to changes in land use (e.g., deforestation) and land management practices (e.g., drainage alteration), resulting in massive amounts of soil carbon loss. Several satellite-borne synthetic aperture radar (SAR) sensors are operating concurrently at different frequencies, providing potentially useful data for monitoring surface motion over tropical peatlands. This study focused on the capability of C-band (SENTINEL-1) and L-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Our subsidence rates were lower than an average of 40 mm/year observed using subsidence poles in an Acacia plantation in Riau (Evans et al, 2019). Our data were in line with peat subsidence rates calculated via InSAR on industrial plantations in South East Asia of 26 ± 17 mm/year (Hoyt et al, 2020), and 14.1 to 26.5 mm/year in the Bengkalis area during 2018–2019 (Umarhadi et al, 2021). Khasanah and van Noordwijk (2019) reported that newly established oil palm had a peat subsidence rate of 47 mm/year while the remnant forest was 18 mm/year and other land‐use types subsided by 2–3 mm/year.…”
Section: Discussionsupporting
confidence: 89%
“…Our subsidence rates were lower than an average of 40 mm/year observed using subsidence poles in an Acacia plantation in Riau (Evans et al, 2019). Our data were in line with peat subsidence rates calculated via InSAR on industrial plantations in South East Asia of 26 ± 17 mm/year (Hoyt et al, 2020), and 14.1 to 26.5 mm/year in the Bengkalis area during 2018–2019 (Umarhadi et al, 2021). Khasanah and van Noordwijk (2019) reported that newly established oil palm had a peat subsidence rate of 47 mm/year while the remnant forest was 18 mm/year and other land‐use types subsided by 2–3 mm/year.…”
Section: Discussionsupporting
confidence: 89%
“…In the future, we expect that the number of satellite data will increase and more extended observation periods permit us to study more precisely the long‐term trends of topographic evolutions. The InSAR time‐series can be considered since it can minimize decorrelation as well as atmospheric artifacts using a stack of multitemporal SAR images (Lu et al, 2007; Umarhadi et al, 2021). Furthermore, the use of multiple acquisition images from different orbits, for example, ascending/descending, and from different satellites, for example, SENTINEl‐1 and ‐2 (e.g., Yanagiya & Furuya, 2020), would allow decomposing the displacement vectors and improve the estimation of the ground deformation with respect to annual and seasonal changes.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of water is critical to ecosystem function in wetland ecosystems and these new spaceborne technologies provide an avenue of opportunity to monitor inundation extent and duration. The ability to model and monitor important ecosystems, which are traditionally difficult to sample in-situ, would benefit existing approaches to measuring peat dome presence and subsidence [19,20] and will be an important advancement in monitoring the health of ecosystems at the forefront of climate change impacts. Currently, approximately 15,000 repeat tracks are available globally (1387 per cycle), with more expected as ICESat-2 continues to collect data.…”
Section: Opportunities For Understanding Ecosystem Functionmentioning
confidence: 99%